2021
DOI: 10.1016/j.hrtlng.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Is prognostic nutritional index a predictive marker for estimating all-cause in-hospital mortality in COVID-19 patients with cardiovascular risk factors?

Abstract: Background: This study examined the possible association between the prognostic nutritional index (PNI) and in-hospital mortality rates in cases with a high cardiovascular risk burden and hospitalized with the diagnosis of coronavirus disease 2019 . Material and Methods: This retrospective and cross-sectional study included 294 COVID-19 patients hospitalized in a tertiary referral pandemic center. The study cohort was grouped into tertiles based on the initial PNI values as T1, T2, and T3. The PNI was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
3
28
1
Order By: Relevance
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 Finally, eight observational studies, with a total of 2002 patients, were included. 8 , 16 , 17 , 33 , 34 , 35 , 36 , 37 However, one study did not report the adjusted OR of PNI as a continuous variable 33 and thus was not included in the meta‐analysis (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] When integrating the effects of both albumin and lymphocyte, it can be intuitive to hypothesize that the PNI could serve as a simplified means of rapid prognosis assessment in COVID-19 patients. 16,17 Consistent with this concept, a recent study demonstrated that the PNI was an essential discrimination indicator for the severity of COVID-19. 16 Additionally, in a study conducted by Çınar et al, 17 the PNI was an independent predictor for in-hospital mortality in patients with COVID-19.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore, the prognostic value of the PNI in patients with COVID-19 is worth further investigation. However, to date, the relevant studies have mainly focused on crude analyses rather than establishing a systematic, quantified model; hence, the application value of the present PNI is extremely limited [14,15].…”
Section: Introductionmentioning
confidence: 99%